A NUMERICAL AND AN EXPERIMENTAL INVESTIGATION OF A HIGH-PRESSURE DIE-CASTING ALUMINUM ALLOY - EKİCİ, BÜLENT (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
In this paper, a computer simulation of a high-pressure die casting of aluminum alloy was performed using a commercially available software and also compared with the real castings of the same alloy. The commercial aluminum alloy was Etial 150 (AlSi12Cu) that is used for flange which is a washing machine part. Mold filling, solidification, temperature distribution, porosity, and velocity of the liquid metal during high-pressure die casting were investigated using the model through numerical simulation. The simulation results proved that the model values used in simulations were accurate in order to apply for experimental casting. After this numerical model, the flange part was cast experimentally according to the obtained optimum parameters from simulation results. Then, specimens from the experimental casting were tested for tensile, hardness, and microstructure analyses. Accordingly, the test results are rather sound which demonstrates that simulation provides profitable die casting. Consequently, it was observed from this study that simulation is not only useful for enhancing casting quality but also very economical and practical, which helps to reduce time spent on experiments. Moreover, simulation can reveal porosity and helps to minimize this defect. Thus, computer simulation should be used for casting applications more often, and simulation programs should be developed further.
Keywords: high-pressure die casting; casting simulation software; casting simulation; casting metallurgy of aluminum alloy; etial 150; mechanical properties; etial 150 high-pressure die casting; properties of Etial 150 casting; AIR ENTRAPMENT; FLUID-FLOW; SOLIDIFICATION